Application of Blended Learning Model Flipped Classroom Era New Normal to Student Learning Outcomes Class IX D SMP Negeri 2 Batu - Eliza Dewi Armelia; Siti Inganah (Justek : Jurnal Sains dan Teknologi, 2022)
Abstract:  This study aims to describe the effectiveness of the application of blended learning model flipped classroom new normal era on student learning outcomes IX D SMP Negeri 02 Batu. This study uses a qualitative approach with a descriptive type of research with the subject of 31 students of class IX D SMP Negeri 02 Batu. Data collection techniques in the form of observation and tests. The data analysis technique is descriptive qualitative. The results showed that the application of blended learning model flipped classroom new normal era was effectively used on the learning outcomes of quadratic equations for class IX D SMP Negeri 02 Batu. The average result of the final score of the pre-test was 72.58 with classical completeness of 61.29%, an increase in the average final score of the post-test was 79.58 with classical completeness of 87.10% in the very good category.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan efektivitas penerapan blended learning model flipped classroom era new normal terhadap hasil belajar siswa IX D SMP Negeri 02 Batu. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif dengan subjek 31 siswa kelas IX D SMP Negeri 02 Batu. Teknik pengumpulan data berupa observasi dan tes. Teknik analisis data berupa deskriptif kualitatif. Hasil penelitian menunjukkan penerapan blended learning model flipped classroom era new normal efektiv digunakan terhadap hasil belajar materi persamaan kuadrat siswa kelas IX D SMP Negeri 02 Batu. Hasil rata-rata nilai akhir pre-test sebesar 72,58 dengan ketuntasan klasikal 61,29% mengalami peningkatan pada hasil rerata akhir post-test yaitu 79,58 dengan ketuntasan klasikal 87,10% dalam kategori sangat baik.